Rapid definition of five novel HLA-A*3002-restricted human immunodeficiency virus-specific cytotoxic T-lymphocyte epitopes by elispot and intracellular cytokine staining assays. - Goulder, P; Addo, M; Altfeld, M; Rosenberg, E; Tang, Y; Govender, U; Mngqundaniso, N; Annamalai, K; Vogel, T; Hammond, M; Bunce, M; Coovadia, H; et al. (2001)
Human immunodeficiency virus (HIV)-specific cytotoxic T lymphocytes (CTL) play a major role in control of viral replication. To understand the contribution of this antiviral response, an initial step is to fully define the specific epitopes targeted by CTL. These studies focused on CTL responses restricted by HLA-A*3002, one of the HLA-A molecules most prominent in African populations. To avoid the time-consuming effort and expense involved in culturing CTL prior to defining epitopes and restricting alleles, we developed a method combining Elispot assays with intracellular gamma interferon staining of peripheral blood mononuclear cells to first map the optimal epitopes targeted and then define the HLA restriction of novel epitopes. In two A*3002-positive subjects whose CTL responses were characterized in detail, the strongest response in both cases was to an epitope in p17 Gag, RSLYNTVATLY (residues 76 to 86). Using this method, CTL epitopes for which there were no motif predictions were optimized and the HLA restriction was established within 48 to 72 h of receipt of blood. This simple and convenient approach should prove useful especially in the characterization of CTL responses specific to HIV and other viruses, particularly in localities where performing cytotoxicity assays would be problematic.